2006
DOI: 10.1186/1471-2334-6-58
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of invasive pneumococcal disease and number of excess cases due to influenza

Abstract: BackgroundInfluenza is characterized by seasonal outbreaks, often with a high rate of morbidity and mortality. It is also known to be a cause of significant amount secondary bacterial infections. Streptococcus pneumoniae is the main pathogen causing secondary bacterial pneumonia after influenza and subsequently, influenza could participate in acquiring Invasive Pneumococcal Disease (IPD).MethodsIn this study, we aim to investigate the relation between influenza and IPD by estimating the yearly excess of IPD ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 27 publications
3
63
1
3
Order By: Relevance
“…This is distinct from concomitant viral/bacterial infection and is usually caused by S. pneumoniae infection preceded by influenza [45]. There is typically a lag time of 2-4 weeks between the two infections, and a study indicates that 12-20% of seasonal cases of invasive pneumococcal disease can be attributed to prior influenza infection [46]. Data from the 2009 influenza A (H1N1) pandemic indicate that other bacterial pathogens associated with influenza A infection include S. aureus, Gram-negative rods and group A streptococcus [47].…”
Section: Discussionmentioning
confidence: 99%
“…This is distinct from concomitant viral/bacterial infection and is usually caused by S. pneumoniae infection preceded by influenza [45]. There is typically a lag time of 2-4 weeks between the two infections, and a study indicates that 12-20% of seasonal cases of invasive pneumococcal disease can be attributed to prior influenza infection [46]. Data from the 2009 influenza A (H1N1) pandemic indicate that other bacterial pathogens associated with influenza A infection include S. aureus, Gram-negative rods and group A streptococcus [47].…”
Section: Discussionmentioning
confidence: 99%
“…This Canadian study finds that influenza notifications Granger‐cause IPD, consistent with our observed lagged relation by plain cross‐correlation analysis, but yearly phase and amplitude terms of the fitted sine waves to the two time series were not correlated19—paralleling our result that (pre‐whitened) residuals were not correlated. Actually, most studies not correcting for autocorrelation report a temporal association between either influenza and/or RSV with IPD incidence 5, 18, 20, 25, 28, 29. Strikingly, the study in children up to 16 years of age by Toschke et al., taking into account temporal autocorrelation, showed no association between influenza outbreaks and invasive pneumococcal infection 27.…”
Section: Discussionmentioning
confidence: 98%
“…RSV and IPD are associated in infants/children,5, 17, 26, 29, 30 and influenza and IPD in the elderly 26, 28, 30. The strongest associations between respiratory viruses and pneumococcal disease occur among the older age groups 18, 20, 22, 26. We could not analyse RSV nor influenza incidence: routine virological testing in the Netherlands, carried out only on sampled ILI patients, gives insufficient power for a time‐series analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported with 7-21 days of lag time for the onset of bacterial infection following seasonal inluenza. However, shorter times from onset to death have been noticed in pandemic periods [67][68][69].…”
Section: Adjuvant Therapy To Treat Secondary Bacterial Superinfectionmentioning
confidence: 99%